HIGHER EDUCATION IN JAPAN: OLD PERIOD AND INNOVATIONS OF PRESENT TIME (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article explores the historical development and contemporary innovations of higher education in Japan. Tracing its origins from Confucian academies in the Nara period to the establishment of modern universities in the Meiji era, the study examines the significant milestones and reforms that have shaped the Japanese higher education system. The post-war period saw the democratization and expansion of higher education, leading to the creation of numerous national and private institutions. In recent years, Japan has focused on internationalization, technological advancements, and educational reforms to address contemporary challenges such as an aging population and the need for a skilled workforce. By integrating historical analysis with an examination of current trends, this article highlights the continuous evolution and modernization of higher education in Japan, emphasizing its efforts to remain competitive and relevant on the global stage.